Mental Health Services for Two Issues Identified in School Adolescents Medellin Colombia (2015)
ABSTRACT: The purposes of the study was identifying the perceptions of mental health services and determine the distribution of depressive symptoms and alcohol use among adolescent students in the northwestern area of Medellin, 2010. Methods: a mixed study is done by selecting a random sample of 605 high school students and interview four directors of health institutions in the Social State Enterprise -Metrosalud and the Mental Health director of the Health Department of Medellin. Findings: problematic prevalence in depressive symptoms and consumption of alcoholic beverages are evident. There statistical association between the two. Only these issues are addressed in the crisis. Conclusion: There is no definite offer mental health services for adolescents; these issues are addressed in consideration when the crisis appears.